Qualität in der Befundung von Kopf- und Halssonographien an Universitätskliniken – eine Stichprobe - Künzel, J.; Bozzato, A.; Ernst, B. P.; Fuhrmann, T.; Ugele, I.; Scherl, C.; Schapher, Mirco; Volk, G. F.; Mansour, N.; Knopf, A.; Bohr, C.; Hamann, K. F. (HNO, 2021)
Background: Ultrasound diagnostics are widely used and are standard for radiologists, otolaryngologists, and oral and maxillofacial surgeons in the diagnostic work-up of various pathologies. There is agreement that digital documentation is urgently needed at present to improve and standardize the quality of sonographic documentation. There are more and more publications on the implementation of standardized documentation of findings in imaging diagnostics, including head and neck sonography. Objective: The present work aims to determine the quality of routine head and neck sonography findings on a random basis, according to the criteria of the Bavarian Association of Statutory Health Insurance Physicians (KVB) at a selection of German university otolaryngology departments (ENT). Materials and methods: A total of 70 randomly selected anonymized written findings including image documentation from seven ENT departments were retrospectively analyzed by an experienced KVB examiner concerning fulfilment of KVB criteria. The data were evaluated descriptively. Results: Of the 70 reports, 69 were eligible for evaluation. The average documentation completeness was 80.6%. A total of 9 findings were correctly documented in full (13%). The documentation completeness of the individual departments was sorted in ascending order from 68.1% to 93%. With 88.5% vs. 75%, the hospitals with a structured report showed a higher level of completeness. In 75% of the cases the hospitals with structured reports also had digital solutions for reporting and image archiving. Conclusion: In general, there is potential for optimization regarding the completeness and quality of routinely prepared head and neck sonography findings at the selected university ENT departments. The implementation of structured reporting masks and the conversion of analogue documentation into digital solutions as well as digital networking with the hospital information systems, picture archiving and communication systems should be promoted. Supervision by senior doctors is required to ensure the quality of findings of inexperienced colleagues and to help to achieve standards in reporting.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Completeness of findings; Digital documentation of findings; Quality of findings; Structured reporting; Ultrasound training